THE FORMATION OF IT COMPETENCE OF THE ACADEMIC STAFF IN A THREE LEVEL SYSTEM OF HIGHER EDUCATION - T. A. Boronenko; V. S. Fedotova (Образование и наука)
The aim of the study is to discuss organizational and methodical bases of formation of ICT competence graduate in the third stage of higher education.Methods. Theoretical methods involve analysis and synthesis, induction and deduction, comparison and classification methods, and empirical method of observation.Results. Trends in the selection of the content of the educational program of graduate students at the third level of higher education in the formation of IT competence are presented: education of the valuable relation to the use of IT in professional activities; the formation of readiness to use IT in education and scientific research; the development of IT skills for processing and visualization of experimental data; modeling of processes and phenomena of professional activities; preparation of the teaching staff to the creation of a new information and educational environment among educational organizations; the development of new social and educational role, forming a system of knowledge and skills of students in the field of information; the development of ready-to-use information technology in the management of education. The discipline content «Information and communication technologies in education and research activities» is selected in accordance with a preferred direction of formation of IT competence. Target indicators and indicators of graduates’ IT competences are developed.Scientific novelty. The concept of IT competence of the teaching staff is introduced. The model of discipline «Information and communication technologies in education and research activities» is designed on the basis of evolutionary development of ICT competence of graduate students in the two-level system of higher education content.Practical significance. The proposed content of the course «Information and communication technologies in education and research activities» which is the basis for the formation of IT competence of the teaching staff at the third level of higher education, allows to generate future teachers’ and researchers’ skills integration of different types of activity (training, educational research, educational, methodical, scientific research, organizational) within a unified methodology based on the use of IT.